15 A model for practice implementation of a person-centred approach to carer assessment and support within palliative care (plan, pilot, train, sustain). Issue 3 (1st September 2017) - Diffin, Janet; Ewing, Gail; Rowland, Christine; Grande, Gunn
Abstract : Introduction: The Carer Support Needs Assessment Tool (CSNAT) intervention ensures a person-centred approach to carer assessment and support within palliative care. 1–3 An online toolkit has been developed to prepare and support organisations with implementation of the CSNAT intervention in palliative care practice. Aims: To test the feasibility of an online toolkit to assist organisations with implementation of a person-centred approach to carer assessment and support within palliative care. Methods: The Plan, Pilot, Train, Sustain model has been developed from the on-going CSNAT research programme; based on feedback from 89 organisations supporting carers using the CSNAT intervention. This model underpins the online toolkit which consists of two learning components: (i) to provide practitioners with the knowledge to use the CSNAT intervention, (ii) to assist organisations to plan, pilot and sustain the use of the CSNAT intervention. Seven organisations have been recruited to a feasibility study (due to conclude June 2017). Up to 20 practitioners will provide feedback on toolkit content and online user experience via a survey and qualitative interview. Results: Feasibility results will be reported: how informative and useful the content is, and how suitable it is for use within existing resources of palliative care services (e.g. time to complete, IT resources). This will enable refinements to toolkit content and instructions. Conclusions: This online toolkit will assist services to respond to the increasing pressures to assess and address the support needs of family carers by providing accessible and structured guidance on how to implement the CSNAT intervention, and help ensure embedding into practice. References: . Ewing G, Grande G. Development of a Carer Support Needs Assessment Tool (CSNAT) for end-of-life care practice at home: A qualitative study. Palliative Medicine2013;27(3):244–256. . Ewing G, Brundle C, Payne S, Grande G. The Carer Support Needs Assessment Tool (CSNAT) for Use in Palliative and End-of-life Care at Home: A Validation Study. Journal of Pain and Symptom Management2013;46(3):395–405. . Ewing G, Austin L, Diffin J, Grande G. Developing a person-centred approach to carer assessment and support. British Journal of Community Nursing2015;20(12): 580–584.